Pengaruh Kesadaran Wajib Pajak dan Pemahaman Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dengan Niat Bayar Sebagai Variabel Mediasi - Maura Wulan; Amelia Setiawan; Hamfri Djajadikerta (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2026)
This study aims to measure the effects of taxpayer awareness and tax understanding on taxpayer compliance, with paying intention serving as a mediating variable. This study employs a casual quantitative approach utilizing data gathered via online Likert-scale questionnaires from 107 individual taxpayer respondents residing in the Waterfront Lippo Cikarang Cluster. Data were analyzed using SmartPLS 4 through PLS-SEM, encompassing evaluations of the outer model, inner model, and bootstrapping. The evaluation results indicate that all indicators meet the criteria for validity and reliability. Taxpayer awareness has a positive effect on paying intention (Beta = 0.210; p = 0.019), tax understanding exerts a more dominant impact on paying intention (Beta = 0.591; p = 0.000), and paying intention influences taxpayer compliance (Beta = 0.447; p = 0.005). The R-square values indicate that awareness and understanding is explain 49.7% of the variance in paying intention, while compliance is explained by 20%. Furthermore, paying intention mediates the effect of tax understanding on compliance (Beta = 0.264; p = 0.018), but it does not mediate the effect of taxpayer awareness (Beta = 0.094; p = 0.069).